Experimental study for evaluating the performances of thermoelectric generator under steady-state and dynamic conditions - Chiang, Trevor Kai Teng (Nanyang Technological University, 2023)
Thermoelectric generator (TEG) is a device that converts heat into electricity by the amalgamation of Seebeck, Joule and Thomson effects plus heat conduction between two ends of a thermoelectric device. The first thermoelectric effect discovered by Thomas Johann Seebeck in 1821 brought about further development and studies of thermoelectricity and thus, the invention of today’s TEG. As compared with vapor/gas power cycle, the thermoelectric generator generates relatively lower power output with the efficiency ranging from 1% to 5% depending on the input heating source. However, in recent years, with the growing demand for sustainable and clean energy sources, there has been a surge in research interest towards the development of thermoelectric generators due to their ability of converting waste heat into electrical power. The main objective of this project is to conduct an experimental investigation into TEG’s operational cycle from transient to steady-state, and to evaluate the TEG’s performance parameters (power and efficiency) for various pulsing and non-pulsing periods. Hence the power generation under non-pulsing indicates the recovery of waste heat i.e., the utilization of thermoelectric thermal energy, which provides a new research direction as environmental sustainability. In this experiment, the performance parameters are evaluated as a function of high-to-low input thermal energy, pulsing and non-pulsing periods and the duty cycle. The experimental results have determined that pulsed heating provides higher efficiency, and the efficiency enhancement of 34.13% is observed as compared to those obtained under steady-state heating conditions. By increasing the heat input duration, efficiency is increased up to the heat recovery region. An increase in high-to-low energy inputs show better performances of the TEG.